An Assessment of Supplier Development Practices in a Retail Environment with Particular Reference to Boots the Chemist - Clarke, Adrian John (2007)
An organisations ability to control, adapt and improve its supply chain can significantly impact its competitive position (Drucker, 1982). For retailers, the supply base contributes almost three quarters of their total costs. Within manufacturing, organisations have been moving from predominantly adversarial, short-term, transactional relationships with their suppliers, to longer-term collaborative relationships. Automotive manufacturers in Japan were leading this, and it has since transferred to western manufacturing organisations. Supplier development has been a pillar of these collaborative relationships, and is defined as - Any set of activities undertaken by a buying firm to identify, measure and improve supplier performance and facilitate the continuous improvement of the overall value of goods and services supplied to the buying companys business unit(Krause et al 1998). Within this definition are two distinct types of engagement. The first is externalised supplier development, where the customer measures performance, and provides incentives for the supplier to improve. The second is internalised. In this case the supplier provides resource and investment to enable them to improve. Whilst there is much literature on supplier development activity in the manufacturing sector, there is relatively little on retail supplier development.